Analysis of The Level of Understanding of Injury Handling in Female Football Athletes at STKIP Pasundan - Meyysi Ayu Ningrum; Gugun Gunawan; Indra Sholehudin (Journal of Physical and Outdoor Education, 2025)
This study aims to analyze the level of understanding of injury management among members of the Women's Football UKM at STKIP Pasundan. A quantitative approach with a descriptive survey design was used. Data were collected through a closed-ended questionnaire distributed to 20 active athletes. The results showed that respondents’ understanding was categorized as "good" (30%), "fair" (55%), and "poor" (15%), with a mean score of 38.80 and standard deviation of 11.37. The understanding of acute injuries was higher (mean = 9.20) than chronic injuries (mean = 7.85). These findings emphasize the need for enhanced education and practical training in injury management for student athletes.